IMPLEMENTASI KEGIATAN LITERASI MEMBACA PADA AWAL PEMBELAJARAN BAHASA INDONESIA UNTUK MENDUKUNG KETERAMPILAN MENULIS EKSPOSISI SISWA KELAS IX MTSN KARO TAHUN AJARAN 2025/2026 - Mazidah Zahra Ramadani Br Limbong; Khairil Ansari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of reading literacy activities at the beginning of Indonesian Language learning and their relationship to the expository writing skills of ninth-grade students at MTsN Karo in the academic year 2025/2026. The study was motivated by the suboptimal use of reading literacy activities in supporting students' writing skills, particularly in composing logical and systematic expository texts. A mixed methods approach with an Exploratory Sequential Design was employed. Data were collected through observation, interviews, documentation, and expository writing tests. The research subjects consisted of all 20 students in class IX-8 at MTsN Karo. The results indicate that reading literacy activities had been implemented routinely for 15 minutes at the start of each lesson; students achieved an average score of 76.5 in expository writing, classified in the good category; however, student engagement was uneven and the integration between reading literacy and writing instruction had not been optimized. This study concludes that reading literacy activities have a positive relationship with expository writing skills, though more targeted strategies are needed to maximize their benefits.